PENGEMBANGAN MODUL PRAKTIKUM LAJU REAKSI BERBASIS INKUIRI TERBIMBING - Amarlita, Dhamas Mega (FKIP Universitas Wisnuwardhana, 2019)
Chemistry practical is really needed in teaching and learning process of chemistry subject. This practical work may given the opportunity for the students to participate in teaching and learning process actively. One of the most valuable media which can be used in this practical work is module based of guided inquiry method. Though developing is module in Salahutu district of high school, we can improve the student activity and creativity in managing their practical work. The 4D by Tiagarajan and Semmel model has been used in developing this modul. 4D model is one of the development model which consists of four stapes, they are define, design, develope, and disseminate. Acording to the results of small group experiment, its show that 70% of student has the very good activity and 30% is in good category of managing their practical work. Furthermore, the large group experiment give result that 85,2% of the student manage their practical work ini very good criteria and 14.6% of then doing it in good criteria.